Three-year outcomes of surgical valve replacement with Dafodil™ pericardial bioprosthesis: Dafodil™-1 trial - Hiremath, Channabasavaraj Shivalingaiah; Jain, Anil R.; Garg, Anurag; Maslekar, Atul A.; Gupta, Nirmal K.; Sarkar, Binay Krishna; Bhat, Seetharama; Porwal, Manish; Meharwal, Zile Singh; Mishra, Yugal Kishore; Vaijyanath, Prashanth; Grover, Vijay; et al. (Frontiers in Cardiovascular Medicine, 2024)
Background: The Dafodil™-1 trial was designed to evaluate the clinical safety and performance of Dafodil™ pericardial bioprosthesis for replacing diseased native or prosthetic aortic or mitral valves in patients with advanced valvular heart disease (VHD). Methods: The Dafodil™-1 trial was a prospective, multicenter, first-in-human clinical trial. Patients were enrolled if they had advanced VHD requiring aortic valve replacement (AVR) or mitral valve replacement (MVR) with or without concomitant valve surgery and having surgical risk scores <4%. Major adverse cardiac events (MACE), including all-cause death, myocardial infarction (MI), and stroke; and hemodynamics were analyzed. Results: A total of 136 patients (aortic: 67 and mitral: 69) were enrolled in the trial (with mean age - AVR group: 60.2±8.3 years and MVR group: 49.7±14.4 years). A total of 134 patients (aortic: 66 and mitral: 68) completed the 3-year follow-up (total 300 per 100 patient-years of follow-up). The AVR group demonstrated a significant reduction in the mean pressure gradients from 51.2±24.1 mmHg at baseline to 11.1±6.0 mmHg at the 3-year follow-up (p<0.0001). The mean effective orifice area (EOA) improved from baseline (0.9±0.6 cm2) to 3-year follow-up (1.8±0.4 cm2) (p<0.0001). In the MVR group, the mean indexed EOA increased significantly from baseline (0.7±0.4 cm2/m2) to 3-year follow-up (1.1±0.4 cm2/m2) (p<0.001). There was significant improvement in New York Heart Association functional class and mean SF-12 scores in both groups. The MACE incidence was 2.3% per 100 patient-years (1.3% strokes per 100 patient-years and 1.3% deaths per 100 patient-years) for AVR group and 4.7% per 100 patient-years (0.6% strokes per 100 patient-years and 4.0% deaths per 100 patient-years) for MVR group. No cases of MI, structural valve deterioration and prosthetic valve endocarditis were reported. The AVR and MVR groups achieved 89.6% and 79.7% MACE-free survival, respectively. Conclusions: The Dafodil™-1 trial demonstrated satisfactory outcomes of clinical safety, hemodynamic performance, and quality-of-life metrics. Additionally, no incidence of structural valve deterioration and very low rates of valve thrombosis during the 3-year follow-up period of Dafodil™-1 first-in-human trial indicated acceptable valve durability up to three years and similar outcomes are warranted for longer follow-ups as a primary goal.